Assessment of velum malfunction in children through simultaneous nasal and oral acoustic signals measurements - GUBRYNOWICZ, Ryszard; CHOJNACKA-WĄDOŁOWSKA, Danuta; KONOPKA, Cecylia (Archives of Acoustics, 2007)
The paper describes the results of several year studies on children speech disorders due to distortions of the velopharyngeal closure, resulting in speech hypernasality or hyponasality. Disorders targeted for the assessment include deficits pertaining to cleft palate, paralysis and adenoids hypertrophy. The patient’s nasopharynx status is evaluated by an acoustic method based on a simultaneous measurement of nasal and oral acoustical output during articulation of test utterances containing target speech sounds. A detailed description of the measurements for specific distortions of target sounds is given and their relations to distortions of the velopharyngeal closure are assessed. These evaluations may assist the clinician in targeting functional goals for treatment and follow the progress of speech rehabilitation.